2018
DOI: 10.1016/j.cell.2018.07.041
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 Suppresses RIPK1-Driven Apoptosis and Inflammation during Development and in Aging

Abstract: Aging is a major risk factor for both genetic and sporadic neurodegenerative disorders. However, it is unclear how aging interacts with genetic predispositions to promote neurodegeneration. Here, we investigate how partial loss of function of TBK1, a major genetic cause for amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) comorbidity, leads to age-dependent neurodegeneration. We show that TBK1 is an endogenous inhibitor of RIPK1 and the embryonic lethality of Tbk1 mice is dependent on RIPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
301
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(336 citation statements)
references
References 54 publications
15
301
1
1
Order By: Relevance
“…On the one hand, it promotes the transcriptional upregulation of anti-apoptotic proteins by NF-κB, which protect cells from RIPK1 kinase-independent apoptosis (Wang et al, 2008). On the other hand, it allows the phosphorylation of RIPK1 by IKKα/β- and TBK1/IKKε, which was shown to protect cells from RIPK1 kinase-dependent apoptosis (Dondelinger et al, 2015, 2019; Lafont et al, 2018; Xu et al, 2018; Ting and Bertrand, 2016). While several studies have reported the importance of proper TNF signaling for the maintenance of liver homeostasis and to prevent liver inflammation and inflammation-induced HCC (Luedde et al, 2014), our study did not identify TNF as a driving cytokine in the liver pathology of OTULIN LPC-KO mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, it promotes the transcriptional upregulation of anti-apoptotic proteins by NF-κB, which protect cells from RIPK1 kinase-independent apoptosis (Wang et al, 2008). On the other hand, it allows the phosphorylation of RIPK1 by IKKα/β- and TBK1/IKKε, which was shown to protect cells from RIPK1 kinase-dependent apoptosis (Dondelinger et al, 2015, 2019; Lafont et al, 2018; Xu et al, 2018; Ting and Bertrand, 2016). While several studies have reported the importance of proper TNF signaling for the maintenance of liver homeostasis and to prevent liver inflammation and inflammation-induced HCC (Luedde et al, 2014), our study did not identify TNF as a driving cytokine in the liver pathology of OTULIN LPC-KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptor protein NEMO binds to these linear chains and brings the kinases IKKα and IKKβ to the complex, thereby allowing activation of the NF-κB pathway. NEMO recruitment to the complex also enables activation of the kinases TBK1/IKKε, which may regulate NF-κB activation (Clark et al, 2011; Lafont et al, 2018; Xu et al, 2018). Upon activation, the MAPK and NF-κB pathways drive expression of a large set of genes, including pro-inflammatory genes (Ting and Bertrand, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging hearts work on the edge of disease (Dai, Chen, Johnson, Szeto, & Rabinovitch, 2012;Xu et al, 2018). Aging is associated not only with a progressive decline in physical function, but also with a significant increase in the risk of many disabilities and even death.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scientists began to realize the importance of immune cells in NDs. However, most studies have focused on the nonspecific, innate immune cells (mostly microglia) (Heneka et al, 2013;Hong et al, 2016;Ising et al, 2019;Ito et al, 2016;Keren-Shaul et al, 2017;Labzin et al, 2018;Singhal et al, 2014;Xu et al, 2018). More recently, a few of reports revealed T cells' contributions to NDs (Gate et al, 2020;Jelcic et al, 2018;Lodygin et al, 2019;Shichita et al, 2009;Sulzer et al, 2017;Sun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%